2016
DOI: 10.1530/rep-15-0354
|View full text |Cite
|
Sign up to set email alerts
|

Morphokinetics of cloned mouse embryos treated with epigenetic drugs and blastocyst prediction

Abstract: Time-lapse monitoring of somatic cell nuclear transfer (SCNT) embryos may help to predict developmental success and increase birth and embryonic stem cells (ESC) derivation rates. Here, the development of ICSI fertilized embryos and of SCNT embryos, non-treated or treated with either psammaplin A (PsA) or vitamin C (VitC), was monitored, and the ESC derivation rates from the resulting blastocysts were determined. Blastocyst rates were similar among PsA-treated and VitC-treated SCNT embryos and ICSI embryos, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Sensitivity and specificity are key parameters used to determine the accuracy and efficiency of diagnostic tests [58, 59]. In the context of the present study, sensitivity was defined as the proportion of embryos that developed successfully to the blastocyst and OG stages, whereas specificity was defined as the proportion of embryos that failed to reach these stages.…”
Section: Discussionmentioning
confidence: 99%
“…Sensitivity and specificity are key parameters used to determine the accuracy and efficiency of diagnostic tests [58, 59]. In the context of the present study, sensitivity was defined as the proportion of embryos that developed successfully to the blastocyst and OG stages, whereas specificity was defined as the proportion of embryos that failed to reach these stages.…”
Section: Discussionmentioning
confidence: 99%
“…The final concentration of PsA was prepared by dilution of the stock solutions in the culture or activation media, depending on the experimental procedure. A starting PsA concentration of 5 μM was employed based on earlier reports, 9,28 and the embryos were divided into 3 groups by random: a control group and 2 treated groups (5 μM and 10 μM PsA, respectively). Embryos were exposed to PsA for 4 h for activation, subsequently cultured for 2 h or 8 h, and finally washed in drops of SOFaa culture medium.…”
Section: Epigenetic Modification Treatmentsmentioning
confidence: 99%
“…For the development of somatic cell nuclear transfer (SCNT) embryos, the embryonic stem cell (ESC)-derived rates from the obtained blastocysts and intracytoplasmic sperm injection (ICSI) fertilized embryos were determined with or without treatment of psammaplin A. The results showed that psammaplin A-treated SCNT exerted increased nuclear transfer ESC derivation and blastocyst rates, and further increased embryo delay, which was not necessarily related to the epigenetic effects [73].…”
Section: Pharmacological Activitymentioning
confidence: 99%